Increasing returns and spatial unemployment disparities - Jens Suedekum (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2003)
Standard models of the new trade and location theories usually assume full employment and are thus ill-equipped to study spatial unemployment differences, which in reality are more pronounced that income disparities. Regional labour market theories like the wage curve-approach on the other hand can not endogenously explain the origin of regional economic disparities. We analyse regional agglomeration and regional unemployment in an unified approach by combining a wage curve with an increasing returns technology. We find that regional unemployment rates closely resemble the coreperiphery structure of regional GDP per capita. This matches the stylised facts from EU-15.
Keywords: 330; Regionale Arbeitslosigkeit; Regionale Disparität; Regionale Lohnstruktur; Effizienzlohn; Regionalökonomik; Skalenertrag; Theorie; EU-Staaten